Unintended pregnancy and contraceptive use among women in low- and middle-income countries: systematic review and meta-analysis - Kelemu Abebe Gelaw; Yibeltal Assefa Atalay; Natnael Atnafu Gebeyehu (Contraception and Reproductive Medicine, 2023)
Abstract Introduction Unintended pregnancy is a leading cause of maternal mortality associated with abortion, inadequate contraceptive use, contraceptive failure, and contraceptive discontinuation in low- and middle-income countries. Most unintended pregnancies occur in regions with limited availability of maternal health services, resulting in a significant number of maternal deaths. Therefore, this review aimed to assess the overall prevalence of unintended pregnancy among women using contraceptives in low- and middle-income countries. Method PubMed, Science Direct, Google Scholar, Scopus, and the Ethiopian University Online Library were searched. Data were extracted using Microsoft Excel and analyzed using STATA statistical software (version 14). Publication bias was checked using forest plot, Begg rank test, and Egger regression test. To check for heterogeneity, I2 was calculated and an overall estimation analysis was performed. Subgroup analysis was conducted by study setting, study design, and publication. The Joanna Briggs Institute quality assessment tool was used to assess the quality of each study. We performed a one-time sensitivity analysis. Results Of the 1304 articles retrieved, 23 studies (involving 40,338 subjects) met the eligibility criteria and were included in this study. The pooled prevalence of unintended pregnancy among women using contraceptives in low- and middle-income countries was 44.68% (95% CI: 35.16–54.20; I2 = 99.7%, P < 0.001). Based on subgroup analysis, the pooled prevalence of unintended events was 43.58% (CI: 32.99, 54.173) and 49.93% (CI: 28.298, 71.555) for cross-sectional and cohort studies, respectively. Based on the study design, it was 34.47% (CI: 27.012, 41.933) for community studies and 55.85% (CI: 33.364, 78.339) for institutional studies. Conclusion The overall prevalence of unintended pregnancy was high among women using contraceptives in low- and middle-income countries. Therefore, it is better to pay attention to prevention strategies for unintended pregnancy, such as information and education accessibility and contraceptive utilization.